USE OF NON-PHARMACOLOGICAL PAIN RELIEF METHODS IN LABOR - Bruna Euzebio Klein; Helga Geremias Gouveia (Universidade Federal do Paraná, 2022)
Objective: to analyze the practice of using non-pharmacological pain relief methods during labor. Method: a quantitative and descriptive cross-sectional study developed from December 2019 to September 2020 in a Maternal and Child Nursing Service from southern Brazil. A total of 560 medical charts were analyzed and data collection took place in the institutional database. The Kolmogorov-Smirnov test was used for normality of the variables and, for associations, the t test for independent samples, chi-square or Fischer's exact test. Results: It was found that 164 (29.3%) of the parturients resorted to at least one type of method, the most used being hydrotherapy with 137 (24.5%), change of position with 124 (22.1%) and breathing exercises with 121 (21.6%). There was a significant association (p<0.05) between methods, type of delivery, pregnancy and parity. Conclusion: This study highlights the profile of parturients who benefit from these practices and exposes the low frequency of their use, showing a promising area for studies and continuing education activities.